The effect of sustainability management practice, enterprise risk management, and business strategies on integrated sustainability performance with intellectual capital as a moderating variable - Hesty Erviani Zulaecha; Basri, Yuswar Z.; Augustine, Yvonne; Mulyani, Susi Dwi (Technium Social Sciences Journal, 2021)
This study aims to examine and analyze the effect of sustainability management practice, enterprise risk management, and business strategy on integrated sustainability performance, and to examine and analyze whether intellectual capital can moderate the effect of sustainability management practice, enterprise risk management, and business strategy towards integrated sustainability performance. The control variables in this study: company size, company age, and free cash flow. The moderated regression analysis with panel data is used to hypothesis testing in this study. The sample of this study was 316 observations consisting of 79 manufacturing companies listed on the Indonesia Stock Exchange in the periode 2016-2019.The results showed that sustainability management practice, enterprise risk management, and business strategy have no direct effect on integrated sustainability performance. Also, Intellectual capital strengthens the positive influence of sustainability management practice, enterprise risk management, and business strategy on integrated sustainability performance.